Feminism and Its Impact on the Literature of Love - Uddin, Md. Abu Saleh Nizam (Universitas Negeri Semarang, 2022)
Writers, readers and critics of literature have long been engaged with the appreciation of Feminist characters and Feminist themes in literary texts. But analyzing Feminism itself, to know about its impact on the literature of love is also an area to be explored. When Feminism is studied, we find in it traits opposing the love of mankind, which increases misery for women and others resulting in the decrease and even disappearance of the literature of love, a priceless possession of human beings. Thus, this paper aims at exploring how Feminism is antagonistic to the love of mankind by being prone to exclusionist and utilitarian politics, hostile to men and children, catalytic to separation in family, and indifferent towards rape and illegal men-women physical relationship eventually contributing to the increase of human misery reflected by and resulting in the gradual extinction of the literature of love. In this research thematic analysis was followed applying Bowen Family Systems Theory, Reader-Response Theory and Theory of Phenomenology. The finding of the research may ignite the search of a love-based, family-centric and holistic approach to ensure a misery-free happy life to women which will be reflected in the rejuvenation of the literature of love.